ASSESSING TEACHER-MADE ASSESSMENTS BASED ON HIGHER ORDER THINKING PRINCIPLES - Fanissa Narita, - (2019)
Revised version of the Curriculum 2013 broadens the concept of assessment requiring teachers to measure students' higher order thinking skills. This instruction can be challenging for many English teachers in Indonesia due to their unfamiliarity with the new concept. Therefore, this study emphasizes on investigating principles of higher order thinking skills assessment carried out by teachers in their assessments and the extent to which the assessments meet the criteria of higher order thinking questions. A case study design was applied with two research instruments namely document analysis and interview with teachers. The data were collected in the form of assessments constructed by two teacher participants from different Junior High Schools. The findings reveal that the teachers already integrated principles of higher order thinking assessments in their assessments including the use of stimulus, novelty, contextual material, and thinking-based questions. However, the use of stimulus was not optimized yet due to the absence of problems presented in some test materials. It is supported by the interview findings showing that the teachers seemed not to be aware about crucial function of the principles which can be valuable considerations for them to construct a better higher order thinking skills assessment. Furthermore, although the numbers of higher order thinking skills questions in both teacher-made assessments (30%-40%) have achieved the standard suggested by the government, among three higher order thinking skills (analyzing, evaluating, and creating skill) only analyzing skill dominantly appeared in the form of multiple choices. Regarding this, teacher internal and external factors are significantly contributed to the way they construct the assessments. Thus, strengthening teachers' understanding about the principles of higher order thinking skills assessments and developing their ability to design the assessments are thoroughly needed.